FELL CAVE REINTERPRETED - Martin, Fabiana Maria (My University, 2022)
Abstract: Since first excavated by Junius Bird in 1936-1937, Fell Cave has been a key site for understanding the process of human peopling of Fuego-Patagonia. The recovery of extinct faunal remains in association with hearths and fishtail projectile points -now known to be diagnostic of early occupations- suggested to Bird that the deposits dated to the Late Pleistocene age of the deposits, which was later confirmed by radiocarbon dating. A rock fall apparently sealed those early deposits, separating them neatly from the Holocene occupations. The materials recovered on that campaign are stored at the American Museum of Natural History, New York, USA. After that initial season, many more excavations took place, including a return by Bird 39 years later, producing a new collection now stored at the CEHA, Instituto de la Patagonia, Universidad de Magallanes, Chile. We present here a preliminary study of the earlier bone assemblages, offering some comparisons with other early Fuego-Patagonia sites, and present an alternative interpretation of the significance of the rock fall. Finally, we explore some implications for the chronology and history of occupations of the site.
Keywords: fell cave; junius bird; human colonization; extinct faunas; south patagonia